Surgery in West Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
The results of surgical removal of a porencephalic cyst in an 18-month old child with infantile spasms and hypsarrhythmia are reported from the Departments of Neurology and Neurosurgery, VA Medical Center and University of Florida; the State University of Stony Brook, NY; and University of Michigan Medical School, Ann Arbor, MI.